2022
DOI: 10.1021/jacs.2c02636
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Insight into the Local Structure and Microenvironment of Isolated Co-Motifs in MFI Zeolite Frameworks for Propane Dehydrogenation

Abstract: Embedding metal species into zeolite frameworks can create framework-bond metal sites in a confined microenvironment. The metals sitting in the specific T sites of zeolites and their crystalline surroundings are both committed to the interaction with the reactant, participation in the activation, and transient state achievement during the whole catalytic process. Herein, we construct isolated Co-motifs into purely siliceous MFI zeolite frameworks (Co-MFI) and reveal the location and microenvironment of the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 56 publications
3
76
0
Order By: Relevance
“…21,22,66 A small pre-edge peak below 7710 eV could be an additional signal for the chemical state of Co(II) species in the Co@MFI samples, which is assigned to the low-spin excitation of Co from 1s orbital to 3d orbital. 21,22 It can be seen that the Co K-edge EXAFS spectra of the two Co@MFI samples (Figure 3b) are obviously different from those of Co foil and Co 3 O 4 and show some discrepancy with that of CoO. The observed band at about 1.6 Å is attributed to the first shell scattering of O atoms, 63,67,90 while the band at about 2.75 Å can be due to the second shell scattering of Si atoms.…”
Section: Characterizations Of the Ligand-free-synthesizedmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22,66 A small pre-edge peak below 7710 eV could be an additional signal for the chemical state of Co(II) species in the Co@MFI samples, which is assigned to the low-spin excitation of Co from 1s orbital to 3d orbital. 21,22 It can be seen that the Co K-edge EXAFS spectra of the two Co@MFI samples (Figure 3b) are obviously different from those of Co foil and Co 3 O 4 and show some discrepancy with that of CoO. The observed band at about 1.6 Å is attributed to the first shell scattering of O atoms, 63,67,90 while the band at about 2.75 Å can be due to the second shell scattering of Si atoms.…”
Section: Characterizations Of the Ligand-free-synthesizedmentioning
confidence: 99%
“…In some cases, formation of a metal spinel with a support like SiO 2 and Al 2 O 3 , or post-treatment of a metal-support catalyst with water could be feasible to enhance the interaction between Co and the support. Recently, in situ incorporation of metal ions or oxides into the matrix or framework of a support, especially the zeolite, has been a popular and effective strategy used in various reactions, ,,,,, including the field of alkane dehydrogenation. ,,, The incorporation is generally completed in a one-pot (hydrothermal) synthesis process where metal and support precursors as well as the other materials are placed together in an autoclave. Although the metal loading in a catalyst seems to be relatively independent and tunable as in using this method, the success in the incorporation of a metal into the framework of a support highly depends on the usage of a suitable coordination agent that coordinates with metal ions to avoid its precipitation or hydrolysis in a solution. ,, For example, Yang et al recently synthesized an Fe-incorporated silicate-1 catalyst using ethylenediaminetetraacetic acid (EDTA) as the coordination agent, showing an excellent catalytic performance for EDH .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lee et al suggested that the subnanometer Co 4 O 4 cluster can also dehydrogenate cyclohexane, and Wang et al suggested that isolated CoO sites are active . In other studies, ultrasmall metallic Co was found to be active, , although metallic Co nanoparticles are generally believed to catalyze side reactions such as cracking and coke formation. In recent years, zeolite-supported Co-based dehydrogenation catalysts are also emerging for their enhanced stability and activity. , Due to the small size of these active Co species and the intimate contact with the support, the sites’ local coordination and chemical environment can differ among studies and influence their properties. Additionally, the Co sites can undergo dynamic changes in response to the gaseous atmosphere and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Density functional theory (DFT) has been widely used to study factors affecting catalytic reaction mechanisms, including adsorption conguration, Gibbs reaction energy barrier, reaction transition state, etc. [14][15][16][17][18][19][20][21] Fu et al 22 used DFT for 8T and 48T models with the mGGA-M06-L function to study mono-branched alkanes in HY and HZSM-5 adsorption energies. They concluded that pore connement was critical to adsorbate stability.…”
Section: Introductionmentioning
confidence: 99%